Effectiveness of educational leadership through directors' performance in online higher education. The biggest online university in Spain - Palomino Fernández, José Manuel; Cáceres Reche, María del Pilar; Lara Lara, Fernando; Berral Ortiz, Blanca (Leadership & Organization Development Journal, 2024)
Purpose: The study aims to analyze pedagogical e-leadership in online higher education in Spain through the application of VAL-ED at the International University of La Rioja. Design/methodology/approach: The methodology used to achieve the objectives has been a descriptive and quantitative methodology through a cross-sectional study based on the implementation of the questionnaire: Adaptation of the VAL-ED to the university context, developed by Palomino et al. (2022a). Findings: Indeed, the data obtained allow the authors to affirm how both directors and supervisors, as well as teachers, have been able to evaluate the leadership behavior of directors, compared to the competence standards of VAL-ED, having obtained very positive results that show how their leadership is, without a doubt, oriented to students. Given the fact that in the second specific objective the study sets out to determine to what extent the three groups of respondents (faculty, supervisors and directors) coincide in the effective performance of the pedagogical leadership of the directors, it can be highlighted that no great differences have been found in the responses of effectiveness obtained from directors, supervisors and teachers, since the results of the resulting scores among these three groups of respondents were reasonably similar.
Keywords: educational leadership; e-leadership; university; Higher Education; students performance; Scopus; WOS